Structural engineering of three-dimensional phononic crystals. (17th February 2016) - Delpero, Tommaso; Schoenwald, Stefan; Zemp, Armin; Bergamini, Andrea
Abstract: Artificially-structured materials are attracting the research interest of a growing community of scientists for the possibility to develop novel materials with advantageous properties that arise from the ability to tailor the propagation of elastic waves, and thus energy, through them. In this work, we propose a three-dimensional phononic crystal whose unit cell has been engineered to obtain a strong wave-attenuation band in the middle of the acoustic frequency range. The combination of its acoustic properties with the dimensions of the unit cell and its static mechanical properties makes it an interesting material for possibly several applications in civil and mechanical engineering, for instance as the core of an acoustically insulating sandwich panel. A sample of this crystal has been manufactured and experimentally tested with respect to its acoustic transmissibility. The performance of the phononic crystal core is remarkable both in terms of amplitude reduction in the transmissibility and width of the attenuation band. A parametric study has been finally conducted on selected geometrical parameters of the unit cell and on their effect on the macroscopic properties of the crystal. This work represents an application-oriented example of how the macroscopic properties of an artificially-structured material can be designed, according to specific needs, by a conventional engineering of its unit cell.